Perilaku Individu dalam Organisasi Pendidikan - Siti Rodiah; Ulfiah Ulfiah; Bambang Samsul Arifin (ISLAMIKA, 2022)
This study aims to describe aspects of human behavior in a particular group which includes aspects caused by the influence of organizations on humans as well as human influences on organizations including organizational behavior. The research method used is in the form of library research with a descriptive-qualitative approach. The results of this study illustrate that there are two factors that influence individual behavior towards educational organizations, namely internal factors and external factors. while the variables of individual behavior analysis include psychological, physiological, and environmental. As a preliminary understanding to understand personal behavior properly, it is necessary to understand the inherent characteristics of the individual, including biography, personality, perceptual characteristics and attitudes. Al-Qur'an verses related to personal behavior become the foundation of educational organizations that humans have positive and negative potentials in behavior, and in essence the positive potential of humans is greater than their negative potential.